การสะสมธาตุอาหารของหญ้าเพ็ดในป่าเต็งรัง - ผ่องอำไพ สมนึก; เรืองพาณิช นิวัติ (วารสารวนศาสตร์ไทย, 2024)
The accumlation and seasonal variation of nutrient content in the aboveground and belowground standing crop of Yaaphet (Arundinaria pusilla Cheval & A Camus) were discussed. The nutrient content of calcium, magnesium, phosphorus, sulfur and potassium of the standing live were higher than that of the standing dead. The nutrients trended to increase in the rainy season up to the early of the dry season and decreased thereafter. Calcium in the litter of Yaaphet trended to increase in the rainy season but potassium and magnesium were decreased. The highest potassium and lowest phosphorus content were found in the aboveground standing crop of Yaaphet on both strata. The amount of accumulation of potassium, calcium, magnesium, sulfur and phosphorus in aboveground standing crop were 26.96, 18.34, 8.51, 3.72 and 2.95 kg/ha on stratum 1 and 22.15, 13.04, 6.58, 3.11 and 2.58 kg/ha on stratum 2 respectively. The calcium content of belowground standing crop of Yaaphet was increased in the rainy season and decreased in the dry season but sulfur and potassium decreased in the rainy season. There were only slightly fluctuation of magnesium and phosphorus content of the belowground standing crop. The maximum amount of calcium and minimum amount of phosphorus were found in the belowground standing crop on both strata. On the average, the accumulation of calcium, potassium, magnesium, sulfur and phosphorus in the belowground standing crop were 78.51, 62.65, 21.63, 12.07 and 10.37 kg/ha on stratum 1 and 79.14, 56.58, 23.67, 11.76 and 9.97 kg/ha on stratum 2, respectively. However, the amount of nutrient contents were very much depend on the belowground standing crop biomass of Yaaphet since the ratio of the aboveground to belowground biomass was 1:2.3